2004
DOI: 10.1046/j.1445-1433.2003.02891.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of colorectal cancer patients in Australia: the National Colorectal Cancer Care Survey

Abstract: With the considerable resources required to develop clinical practice guidelines, studies like this are essential to monitor the impact of the guidelines. To ensure that the guidelines are in line with current evidence, regular reviews of the guideline recommendations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 93 publications
0
26
0
Order By: Relevance
“…1 Nationally, Australia has an emergency CRC rate of 10.7 percent. 10 Patients in this study lived in the southwestern part of Sydney with a high proportion of recent migrants. From 1997 to 2004, the rate for emergency operation has averaged 15.8 percent and shows no sign of decreasing (range, 12.6-17.7 percent; trend test P=0.96).…”
Section: Discussionmentioning
confidence: 99%
“…1 Nationally, Australia has an emergency CRC rate of 10.7 percent. 10 Patients in this study lived in the southwestern part of Sydney with a high proportion of recent migrants. From 1997 to 2004, the rate for emergency operation has averaged 15.8 percent and shows no sign of decreasing (range, 12.6-17.7 percent; trend test P=0.96).…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of all studies was to document the surgical management and patient outcomes in their populations. Two reports documented outcomes for the same study [10,11]. In summary, the range of published adverse events used to populate our model were 0.5-2.8% for anastomotic leaks, 2.1-9.1% for wound infections, 0.3-6.7% for DVT, 2.7-12.2% for return to theatre, 0.2-10.7% for respiratory conditions and 0.2-7.7% for 30-day deaths.…”
Section: Resultsmentioning
confidence: 99%
“…This rate was considered an outlier and omitted from our summary estimates. Five studies, including three in NZ [12-14], reported outcomes from regional areas [4,12-15] while the remainder were state-wide [16], national [10,11,17] or urban-based [18,19]. One study accounted for pre-operative factors and outcomes were risk-adjusted [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, many CMS of cancer patients have been undertaken, and many have been large, with high response rates, and based on patients drawn from population-based cancer registries. There have been national CMS for breast1 2 and colorectal cancer3 4 and surveys at a state or territory level for many other cancer sites. A descriptive review of all published CMS up to 2003 forms the base for this study 5.…”
mentioning
confidence: 99%